Musāhamat Ta‘allum al-Lughah al-‘Arabiyyah fī Tanmiyat al-Dhakā’ al-‘Aqlī - Wardah Nailah El-izzah Atulolon; Safira Budiaty Nafi'a; Ade Irvan; Khoirun Nisa; Amanda Putri; Syaiful Mustofa (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
Arabic is often perceived merely as a tool for religious communication; however, its rich semantic structure, systematic grammatical logic, and demanding usage require precision of thought and sharp analytical skills. This study aims to explain the role of Arabic language learning in enhancing intellectual intelligence, focusing on learning processes that strengthen cognitive aspects and activities that foster such development. Employing a descriptive qualitative approach through literature analysis and in-depth interviews, the data were interpretively examined to reveal the relationship between language-learning activities and students’ cognitive growth. The findings indicate that problem-solving abilities improve through activities such as developing instructional media, participating in Qira’atul Kutub competitions, and undertaking TOAFL training, all of which demand accuracy and rapid analysis. Practical intelligence develops through Muhadatsah Yaumiyah, reading exercises (Qira’ah), and mastery of word inflection (Tashrif), which cultivate cognitive flexibility. Verbal integration is reinforced through Arabic debates (Munazarah), speech training (Khitobah), and news reading (Qira’atul Akhbar), requiring precise diction and coherent argumentation. This study highlights the holistic contribution of Arabic to three key components of intellectual intelligence by integrating theoretical analysis with field-based evidence.